Frequency-dependent multiconductor line model based on the Bergeron method - Caballero, Pablo Torrez [UNESP]; Costa, Eduardo C. Marques; Kurokawa, Sérgio [UNESP] (Elsevier, 2015)
A new multiconductor transmission line model is proposed based on the method of characteristics. The conventional Bergeron model is characterized by the line representation using constant lumped parameters. The novel content of this paper is the inclusion of the frequency effect in the longitudinal parameters by fitting techniques and three-phase representation of the Bergeron line model. This new feature enables to extend the application of the Bergeron method for simulation of electromagnetic transient in three-phase systems, considering fast and impulsive transients composed of a wide range of frequencies.
Keywords: Electromagnetic transients; Time-domain analysis; Transmission line modeling; Vector fitting